Analisis Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (surve pada cafe kedai mat moen diboyolali) - Janun R.S, Burhan; , Basworo Dibyo, SE., M.Si (2017)
The objectives of this study was to determine the effect of price on customer satisfaction at Café Coffee Matt Moen. To determine the effect of product quality to customer satisfaction at Café Coffee Matt Moen.To determine the effect of service quality on customer satisfaction at Café Coffee Matt Moen. The population used in this study is a community in the town of Boyolali who've been to Café Coffee Mat Moen are huge numbers. While the sample the researchers counted 100 people. Based on these results the variable price has a significant influence on customer satisfaction. The variable quality of the product has a significant effect on customer satisfaction. Service quality variables have a significant influence on consumer satisfaction. While the F-test results obtained F count> F table (34.404> 3.15), then Ho is rejected, Means jointly variable price, product quality and service quality together to customer satisfaction, so that the model can be used in the research is fit. The result of the calculation to the value of R2 obtained in multiple regression analysis obtained with a coefficient of determination adjusted- R2 of 0.503. This means that 50.3% customer satisfaction variable variation can be explained by the variable price, product quality and service quality while the remaining 49.7% is explained by other factors outside the model studied.